Professional competences for the touristic shop assistants: formative approach in Cuba - Balido León, Raquel; Cabré Hernández, Roquelina Jakeline; López Ramírez, María Teresa (Transformación, 2024)
Objective: This article aims at recognizing the potential and limitations of the formative process of tourist shops assistants at the Tourism Training Center Villa Clara province.Methods: Different methods and techniques were used, such as: document analysis, interviews, observation of practicing salespeople and experiences of the training process of shop assistants in the Tourism Training Center.Result: The main finding is the description of tourist shops assistants’ professional competencies intended to improve their general and commercial education on the basis of the potentials and limitations identified.Conclusion:  The training process of tourist shops assistants has gone through different approaches in the curricula. The research allows the identification of potentials and limitations of the competency-based education approach that has been introduced recently.
Keywords: Competency-based education; professional training; commercial education; tourism